2004
DOI: 10.1897/03-323
|View full text |Cite
|
Sign up to set email alerts
|

In situ reproduction, abundance, and growth of young‐of‐year and adult largemouth bass in a population exposed to polychlorinated biphenyls

Abstract: We conducted a two-year field study (2000-2001) in the Housatonic River, Massachusetts (USA) to determine if we could detect in situ population-level effects on largemouth bass (Micropterus salmoides) exposed to elevated levels of polychlorinated biphenyls (PCBs). Calculated whole-body PCB concentrations in adult bass in 2002 averaged 121 mg/kg (range = 34-556 mg/kg). Polychlorinated biphenyl concentrations in young-of-year (YOY) composites in 2000 and 2002 averaged 28 mg/kg (range = 21-41 mg/kg) and 19 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
(50 reference statements)
4
8
3
Order By: Relevance
“…The residuals of linear catch-curves were plotted against these year-classes (middle graph) The bottom graphs show the three-year moving average total wet-weight PCB concentrations in muscle tissue of adults against years when these adults were collected and these values correspond to the same time intervals in the top and middle graphs. wet-weight did not exert a population-level effect on largemouth bass recruitment in the Housatonic River, Massachusetts (Reiser et al, 2004), consistent with our results in the Thompson Island Pool.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The residuals of linear catch-curves were plotted against these year-classes (middle graph) The bottom graphs show the three-year moving average total wet-weight PCB concentrations in muscle tissue of adults against years when these adults were collected and these values correspond to the same time intervals in the top and middle graphs. wet-weight did not exert a population-level effect on largemouth bass recruitment in the Housatonic River, Massachusetts (Reiser et al, 2004), consistent with our results in the Thompson Island Pool.…”
Section: Discussionsupporting
confidence: 90%
“…Maximum concentrations of PCBs in largemouth bass were similar between the Housatonic River and our site nearest to the PCB sources in the upper Hudson River during the early 1990s (about 30 g/g wet weight). The data analyzed in this paper for largemouth bass, yellow perch, and brown bullhead, supported the findings of Reiser et al (2004). We did not detect PCB-mediated effects on fish reproduction at the population level at adult PCB concentrations that previously have been thought to be detrimental to these fish species.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…At all of these sites, except the Kalamazoo River, the USEPA concluded that some fish species were at risk from PCB exposures. However, at 3 of the 4 remaining sites, including the Hudson River, apparently healthy populations of at risk species have persisted in spite of exposure to elevated concentrations of PCBs (Munns et al 1997; Barnthouse et al 2003; Reiser et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In populations in which there are large amounts of fish consumption, PCBs can bioaccumulate and noticeably alter physical and motor development [9,10]. Studies on natural animal populations consistently find moderate-to-high levels of PCBs in many diverse animal groups [range in concentration from 3 to 500 ng/g; [11][12][13]] and it is principally unknown as to how this exposure influences development of psychological function. Lower, continuous exposure could be leading to less noticeable insults that impact more complex behaviors.…”
Section: Introductionmentioning
confidence: 99%